Sistem Pemilah Telur Ayam Kampung dan Ayam Negeri Menggunakan Metode Naive Bayes - Hazal Kurniawan Putra; Dahnial Syauqy; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The value demand of chicken eggs in Indonesia is high, in the sector of trading, chicken eggs in Indonesia has dominating the market wich value of 65%, the rest is duck eggs,bird egg and quails eggs. There are two types of eggs, eggs produced by free-range chickens and eggs produced by domestic chickens. The difference between this egg, domestic chicken eggs is heavier than free-range chickens eggs. Because of these parameters, that's will be difficult differentiate between free-range and domestic chicken eggs, and this will take long time and lot of energy. Based of the problem, it is necessary to create a system that can be used to differentiate between free-range chicken eggs and domestic chicken eggs. Using TCS-3200 to measure the level of egg color based on red, green and blue values, and loadcell sensor to measuring egg weight, then it will be classified using the Naive Bayes Method, and status will be printed on LCD, all systems are processed on Arduino. Testing method focused on functionality, accuracy, and system performance. From the functional testing, this system has 100% value, so it can be concluded successful functional testing. For Accuracy testing, the system tested with 40 of training data and test data of 20 data and have accuracy 100%. Testing for performance, the system has an average processing time speed of 754,95 ms.